Biostimulants-Based Amino Acids Augment Physio-Biochemical Responses and Promote Salinity Tolerance of Lettuce Plants (Lactuca sativa L.) - Mostafa Abdelkader; Luidmila Voronina; Lyudmila Baratova; Olga Shelepova; Meisam Zargar; Mikhail Puchkov; Elena Loktionova; Bekzad Amantayev; Assemgul Kipshakbaeva; Bauyrzhan Arinov (Horticulturae, 2023)
Studying the biostimulation effect of amino acids indicated their possible role in salt stress mitigation. In this investigation, six exogenous amino acids (alanine (Ala), arginine (Arg), glutamine (Glu), glycine (Gly), methionine (Met), and proline (Pro)) at 0.5 g/L were sprayed to evaluate their impact on lettuce plants cultivated under simulated salt stress conditions. Photosynthetic pigments, ion absorption, endogenous amino acids contents, catalase (CAT), and peroxidase (POD) enzyme activities were determined. A significant alleviation of salt stress was noticed when EAAs were used in the stress-induced plants, and applying Gly, Met, and Pro improved the plant status under salt stress conditions. The highest electric conductivity (568 μS/g) was testified from the control treatment (50 mM NaCl), while applying exogenous amino acids reduced electrical conductivity (EC), and the result was located between 469 and 558 μS/g. AAs alleviated Cl- anions in the lettuce leaves by 25% in comparison to control plants. Na+ cations were alleviated when the stress-induced plants were sprayed with amino acids. In contrast, applying amino acids promoted K+ uptake, and Arg presented the highest contents (3226 μg/g). AAs promoted chlorophyll (chl a and chl b) concentrations compared to the control treatment, and Met produced the maximum chl a content, while the carotene (car) contents significantly augmented when Gly, Met, and Pro were applied. AAs were highly generated in non-stressed treatment (Std) compared to the control. Under simulated salinity stress, Met and Pro application enhanced proteinogenic amino acids expression. Compared to Ctl treatment, peroxidase enzyme activities significantly diminished in the other treatments, which fell by over 40% when Gly, Met, and Pro were sprayed.